2018
DOI: 10.3749/canmin.1700050
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Major and Trace Elements of Primary WÖhlerite As an Indicator of the Origin of Pegmatites in the Larvik Plutonic Complex, Norway

Abstract: Last but not least, a huge thanks to my family and friends who have continuously supported me over the years. Who knows, maybe one day knowing a little bit about nepheline syenite pegmatites might become useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Nepheline syenite in dykes associated with pegmatites is related to an evolved derivate from RS 6 larvikite (Groome, 2017). Chemical variation between pegmatites situated in larvikite with or without nepheline syenite show that these rocks are related to a common source (Sunde et al, 2018). Furthermore, the major and trace element signature of wöhlerites from the different pegmatites within the Sagåsen quarry are identical, supporting a common source despite their difference in size, orientation, contact relations and mineralogy (Sunde et al, 2018).…”
Section: Timing Of Pegmatite and Nepheline Syenite Emplacementmentioning
confidence: 97%
See 1 more Smart Citation
“…Nepheline syenite in dykes associated with pegmatites is related to an evolved derivate from RS 6 larvikite (Groome, 2017). Chemical variation between pegmatites situated in larvikite with or without nepheline syenite show that these rocks are related to a common source (Sunde et al, 2018). Furthermore, the major and trace element signature of wöhlerites from the different pegmatites within the Sagåsen quarry are identical, supporting a common source despite their difference in size, orientation, contact relations and mineralogy (Sunde et al, 2018).…”
Section: Timing Of Pegmatite and Nepheline Syenite Emplacementmentioning
confidence: 97%
“…Chemical variation between pegmatites situated in larvikite with or without nepheline syenite show that these rocks are related to a common source (Sunde et al, 2018). Furthermore, the major and trace element signature of wöhlerites from the different pegmatites within the Sagåsen quarry are identical, supporting a common source despite their difference in size, orientation, contact relations and mineralogy (Sunde et al, 2018). Therefore, our current knowledge suggests that both nepheline syenite and pegmatites in RS 6 were emplaced within a short, but similar time-frame.…”
Section: Timing Of Pegmatite and Nepheline Syenite Emplacementmentioning
confidence: 99%
“…This is confirmed by subsequent crystal structure refinements in which the Nb site is populated by a significant amount of Mn or Mg (Bellezza et al , 2012; Biagioni et al , 2012). Andersen et al (2010) and Sunde et al (2018) showed only minor chemical variations in wöhlerite from different localities in the Larvik plutonic complex in Norway.…”
Section: Historical Synopsismentioning
confidence: 97%
“…Marianoite was described as monoclinic, P2 1 , with a = 10.846, b = 10.226, c = 7.273 Å and β = 109.33°. The highest Nb content reported by Chakhmouradian et al (2008) for marianoite is 1.019 apfu, which is roughly 0.3 apfu more than in wöhlerite from the Langesundsfjord (Sunde et al, 2018). The approval of marianoite as a valid mineral species was based on the assumption that both Zr and Nb are disordered on the two smallest octahedral sites [average bond lengths: 2.031 (X6) and 2.080 Å (X1)] occurring in the structure.…”
Section: Discreditation Of Marianoitementioning
confidence: 99%
See 1 more Smart Citation